(untitled) (Indian Journal of Animal Production and Management, 2024)
The current study was conducted to study biochemical attributes of Pantja Buck semen. For this purpose six mature healthy bucks were selected from the Goat Unit maintained at Department of Livestock Production Management, College of Veterinary and Animal Sciences, Pantnagar, Uttarakhand (India). All the experimental bucks were kept under similar feeding and management conditions. Semen collection was done early morning by artificial vagina method. Total 36 semen samples were collected for a period of 3 months. Immediately after the collection, samples were examined for biochemical attributes. Overall mean value of pH was found (6.61 ± 0.02) independent of buck age. Resazurin and Methylene blue reduction time were noted higher for younger bucks and minimum for older bucks with overall value 3.15 ± 0.25 and 6.04±0.36 min. respectively. Mean values of HOST and Millovanov’s resistance test were recorded as 36.10 ± 1.17 % and 5216.70 ± 1.94 respectively. 16.76 ± 0.86 % sperms were found resistance to cold shock.